DNA-Free Genome Editing of Brassica oleracea and B. rapa Protoplasts Using CRISPR-Cas9 Ribonucleoprotein Complexes - Murovec, Jana; Guček, Katja; Bohanec, Borut; Avbelj, Monika; Jerala, Roman (Frontiers in Plant Science, 2018)
The CRISPR/Cas9 genome editing system has already proved its efficiency, versatility and simplicity in numerous applications in human, animal, microbe and plant cells. Together with the vast amount of genome and transcriptome databases available it represents an enormous potential for plant breeding and research. Although most changes produced with CRISPR/Cas9 do not differ from naturally occurring mutations, the use of transgenesis during varietal development can still trigger GMO legislation in countries that rely on process-based regulation. Moreover, stable integration of DNA coding for genome-editing tools into plant genomes can result in insertional mutagenesis, while its prolonged expression can cause mutations in off-target sites. These pitfalls can be avoided with the delivery of preassembled ribonucleoprotein complexes (RNPs) composed of purified recombinant enzyme Cas9 and in vitro-transcribed or synthesized sgRNA. We therefore aimed to develop a DNA-free protocol for site-directed mutagenesis of three species of the genus Brassica (B. oleracea, B. napus and B. rapa) with the use of RNPs. We chose cabbage, rapeseed and Chinese cabbage as species representatives and introduced RNPs into their protoplasts with PEG 4000. Four sgRNAs targeting two endogenous genes (the FRI and PDS genes, two sgRNAs per gene) were introduced into all three species. No mutations were detected after transfection of rapeseed protoplasts, while we obtained mutation frequencies of 0.09 to 2.25 % and 1.15 to 24.51 % in cabbage and Chinese cabbage, respectively. In both species, a positive correlation was displayed between the amount (7.5, 15, 30 and 60 µg) of Cas9 enzyme and sgRNA introduced and mutation frequency. Nucleotide changes (insertions and deletions) were detected 24 h after transfection and did not differ 72 h after transfection. They were species-, gene- and locus-dependent. In summary, we demonstrated the suitability of RNP transfection into B. oleracea and B. rapa protoplasts for high-efficiency indel induction of two endogenous genes. Due to the relatively high mutation frequencies detected (up to 24.51 %), this study paves the way for regeneration of precisely mutated Brassica plants without the use of transgenesis.